Short term global health experiences and local partnership models: a framework. Issue 1 (December 2015) - Loh, Lawrence; Cherniak, William; Dreifuss, Bradley; Dacso, Matthew; Lin, Henry; Evert, Jessica
Abstract Contemporary interest in in short-term experiences in global health (STEGH) has led to important questions of ethics, responsibility, and potential harms to receiving communities. In addressing these issues, the role of local engagement through partnerships between external STEGH facilitating organization(s) and internal community organization(s) has been identified as crucial to mitigating potential pitfalls. This perspective piece offers a framework to categorize different models of local engagement in STEGH based on professional experiences and a review of the existing literature. This framework will encourage STEGH stakeholders to consider partnership models in the development and evaluation of new or existing programs. The proposed framework examines the community context in which STEGH may occur, and considers three broad categories: number of visiting external groups conducting STEGH (single/multiple), number of host entities that interact with the STEGH (none/single/multiple), and frequency of STEGH (continuous/intermittent). These factors culminate in a specific model that provides a description of opportunities and challenges presented by each model. Considering different models, single visiting partners, working without a local partner on an intermittent (or even one-time) basis provided the greatest flexibility to the STEGH participants, but represented the least integration locally and subsequently the greatest potential harm for the receiving community. Other models, such as multiple visiting teams continuously working with a single local partner, provided an opportunity for centralization of effortsand local input, but required investment in consensus-building and streamlining of processes across different groups. We conclude that involving host partners in the design, implementation, and evaluation of STEGH requires more effort on the part of visiting STEGH groups and facilitators, but has the greatest potential benefit for meaningful, locally-relevant improvements from STEGH for the receiving community. There are four key themes that underpin the application of the framework:1. Meaningful impact to host communities requires some form of local engagement and measurement 2. Single STEGH without local partner engagement is rarely ethically justified 3. Models should be tailored to the health and resource context in which the STEGH occurs 4. Sending institutions should employ a model that ultimately benefits local receiving communities first and STEGH participants second. Accounting for these themes in program planning for STEGH will lead to more equitable outcomes for both receiving communities and their sending partners.